Static Stability Study of a Shallow Vee Hull Airboat for Sarawak Riverine Application - Yek, Peter Nai Yuh (University Malaysia Sarawak, UNIMAS, 2014)
This research aims to evaluate and explore the alternative of water transport varieties. Sarawak with riverine condition has shown a high potential of airboat application and development prospect as transportation is essential to bring people closer. This research acts as a preliminary work that aims to take a fresh look on the Static stability of existing Shallow Vee hull and follow with the PROLINES simulations for another two types of hull designs, which are Flat Bottom and Modified hull. Centre gravity (KG), metacentric height (GM) and metacentre above centre of buoyancy (BM) have shown the major influencing parameters manipulating the static stability of airboat. Besides that, an airboat with Shallow Vee hull was made for the stability performance testing in UNIMAS’s pool, and it has given an acceptable range of testing results. Rpm of propeller, fuel consumption and wind speed have been measured before hand. Subsequently airboat is operated to measure the average speed and observed the overall stability during the turning. Naval architecture software, PROLINES is used for simulation work of different displacement and type of hulls. Simulation results have evaluated the airboat hydrostatics and statics stability performance. As a result, Flat Bottom and Modified hull gives merits of static stability compared to Shallow Vee hull.